UPAYA PEMERINTAH DAERAH DALAM PENANGANAN PANDEMI COVID-19 DI KABUPATEN GARUT - Rana Putri Kurniawan; Muhammad Alvin Giffary; Wendy Marbun (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2021)
The pandemic that is endemic throughout the world is making every country work hard to eradicate it. has been declared by the World Health Organization (WHO) as a Global Public Health Emergency which is known to spread to all corners of the world very quickly. Coronavirus is a new virus that causes illness ranging from mild to severe symptoms. There are at least two types of corona viruses that cause serious illness, namely Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). Coronavirus disease 2019 (COVID-19) is a new disease that has never been identified in humans. The virus that causes is called SarsCoV2. COVID-19 is a new disease and there is very little research on it. Evidence-based information is required for the care, treatment and other information related to this disease. The Indonesian government later declared the Corona problem as an unnatural or non-natural national disaster. The President of the Republic of Indonesia, regional governments and their staff work together in various efforts to prevent the spread of the virus in the community. From ministerial level to province, district or city Keywords: Pandemic, Local Government, Efforts